Pemikiran Politik Fazlur Rahman dan Abdurrahman Wahid - Hafizatuzzahra Hafizatuzzahra; Rihadatul Aisya Salma; Petia Silfa WP; Zainab Zainab (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The dynamics of Islamic statehood in the modern era face significant challenges due to decolonization and globalization, requiring Muslims to adapt to the nation-state system. This community service activity aims to provide public education regarding the contemporary Islamic political thought of Fazlur Rahman, Abdurrahman Wahid, and Amien Rais. The method employed is Public Education and Interactive Dialogue through a constitutional literacy approach based on Islamic values, encompassing stages from needs identification to in-depth discussion of the figures' thoughts. The results indicate that these three figures offer perspectives that bridge Islamic tradition with modern principles. Fazlur Rahman emphasizes ethical substance through the double movement method, Abdurrahman Wahid promotes inclusiveness within the framework of the Pancasila State, and Amien Rais stresses political morality through the concept of Social Monotheism (Tauhid Sosial). Collectively, they reject extreme secularism and formalistic theocracy by prioritizing justice and humanity. The conclusion of this activity is that integrating Islamic values into the modern state system can strengthen democracy and religious moderation at the community level.